2019
DOI: 10.18280/ria.330105
|View full text |Cite
|
Sign up to set email alerts
|

Design and Application of Face Recognition Algorithm Based on Improved Backpropagation Neural Network

Abstract: Face recognition is a promising technology with a great application potential and broad prospects for development. Compared with other identification technologies, face recognition can achieve rapid and easy sampling, without affecting the behavior of the sampled. These advantages have induced a surging demand and interests in this technology, making it a research hotspot in artificial intelligence. This paper extracts the features from the target face image by Principal Component Analysis (PCA), reducing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…If in the testing process, the image to be tested is an image using glasses, then one of the images using glasses must be entered into the training image database. As in the case with face expressions, and the level of face tilt, there must be an image of a face with several face expressions and the level of face tilt entered in the training image database [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…If in the testing process, the image to be tested is an image using glasses, then one of the images using glasses must be entered into the training image database. As in the case with face expressions, and the level of face tilt, there must be an image of a face with several face expressions and the level of face tilt entered in the training image database [7].…”
Section: Discussionmentioning
confidence: 99%
“…In previous research, the success rate of face image recognition using the Backpropagation method was 98% [6]. Also, other research concluded that the Backpropagation Method with improvised Scaled Conjugate Gradient (SCG) generates average recognition rate of 93% and an average number of iterations of 815 [7]. The KSOM method was chosen because it is one of ANN the most widely used unsupervised learning methods, with a high accuracy value, and a short recognition time process.…”
Section: Introductionmentioning
confidence: 99%
“…In gait recognition, image sequence is the basis of most research methods [11]. The image sequence-based methods generally collect gait information over long distance by camera, and identifies the gait through feature extraction and classification.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The artificial neural network trained using a back propagation (BP) algorithm is most popular and widely used [18]. The evaluation of the artificial neural network is divided into two stages: the first one is feed forward stage and second one is back propagation stage.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%